TINDAK TUTUR DIREKTIF GURU BAHASA INDONESIA DAN RESPON SISWA DALAM PROSES BELAJAR MENGAJAR DI KELAS IX SMP NEGERI 2 AMPEK ANGKEK - Yuridha, Merli; Afnita, Afnita; Tressyalina, Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research is to describe the form of speech act directive, story strategy, politeness, and student's response in teaching and learning process in Ix class of SMP Negeri 2 Ampek Angkek. The type of this research is qualitative descriptive This research was conducted in class IX SMP Negeri 2 Ampek Angkek. Subjects in this study were Indonesian language teachers SMP Negeri 2 Ampek Angkek, Mrs. Desni Yurza and students of class IX SMP Negeri 2 Ampek Angkek. Instruments in this research is the researcher himself. The data that have been collected is analyzed by classifying the data of speech acts directive, srtategi speak, politeness, and student response in teaching and learning process. Based on the research result, it is concluded four things. First, the speech act of the Indonesian language teacher directive in class IX SMP 2 Ampek Angkek can be said is good. Second, the strategy of speaking Indonesian teachers in class IX SMP Negeri 2 Ampek Angkek still needs to be improved. Third, the principle of language-related politeness in the class IX SMP Negeri 2 Ampek Angkek needs to be improved. Fourth, the response of students in class IX SMP Negeri 2 Ampek Angkek to the speech acts of teachers has not happened a good response.Â Kata kunci: direktif, strategi, kesantunan, respon siswa.Â